PENGARUH INTENSITAS PENDIDIKAN AGAMA ISLAM DI LINGKUNGAN SEKOLAH TERHADAP PEMBENTUKAN AKHLAK SISWA KELAS V SD NEGERI GENUKWATU I NGORO JOMBANG TAHUN PELAJARAN 2015/2016 - Churniati, Ida; Mahsun, Ali (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
This article discusses how the intensity of Islamic education in the school environment and how bembentukan Student Morals and How Influence Intensity of Islamic Religious Education in School Environment Against the Formation of Student Morals. This type of research is quantitative research. Variable X is the intensity of Islamic religious education while the variable Y is the formation of morals students. The subjects of this study are students of class V SD which amounted to 39 students, because the population is less than 100 then this study is a population study. This research uses Quantitative Descriptive approach ex post facto and using population technique. And to obtain the author information using the questionnaire method, while the data analysis technique used is theformula Product moment by using the help of SPSS 17 for windows program. After doing research and calculation hence got result that intensity of education of religion of islam in school environment have high intensity equal to 66,7% and student moral formation equal to 59,0%. While the value of the correlation coefficient of both variables is 0.790, is between 0.710 - 0.900 this means very strong closeness (see table 4.6). In the sig (2-tailed) column of 0.000 <0.05. While the result of analysis by using simple regression formula through output of SPSS can be concluded that there is positive and significant influence between Intensity of Islamic Religious Education in School Environment to the Formation of Student Morals in SD Negeri Genukwatu I Ngoro. With the contribution level of the dependent variable (Intensity of Islamic Religious Education) gives influence to the moral formation of 62.5%, and the rest 37,5 (100% -62,5) caused by the influence of other variables outside the variable used.Keywords: Intensity of Islamic Religious Education in School Environment, Formation of Morals